The main misconceptions in cardiology concerning obesity - S. O. Eliashevich; A. S. Ignatiadi; A. P. Misharova; O. M. Drapkina (Рациональная фармакотерапия в кардиологии, 2024)
This article reviews common myths and stereotypes about obesity that distort the understanding of its causes and pathogenesis and contribute to the disease stigmatization among the cardiology medical community. Obesity is a chronic, relapsing, multifactorial disease characterized by excessive formation of adipose tissue, progressing in its natural course and, as a rule, having an increased cardiometabolic risk. For effective prevention of complications, it is necessary to start treating obesity at the risk and pre-disease stages (abdominal obesity and overweight). The causes of obesity include genetic, metabolic, social and environmental factors. The review emphasizes that obesity is not exclusively a consequence of a lack of willpower in choosing food products according to the rules of healthy eating or a sedentary lifestyle. Many stereotypes, such as the idea that all patients with excess body weight have an alimentary genesis of the disease and all clinical "findings" are associated with obesity, do not correspond to reality and hinder effective prevention and treatment strategies. No other chronic non-communicable disease is as stigmatized as obesity. Moreover, despite the development of modern pharmacotherapy, behavioral therapy for obesity, and bariatric surgery, there is high clinical inertia in timely initiation of treatment for this disease. Body weight is becoming the same target indicator in general therapeutic practice as blood pressure or glycemia. Modern medicine dictates the need to rely solely on the evidence base to refute myths in order to create a more inclusive and supportive environment that promotes the health and well-being of patients.